Photo-thermoelastic diffusive waves with microconcentration in quantum-modified semiconductors - Amsawrah M. Mohammed; Eman Ghareeb Rezk; A. H. El -Sharif; Alaa A. El-Bary; Khaled Lotfy (PLoS ONE, 2026)
This study presents a general one-dimensional analysis of photo-thermoelastic diffusive wave propagation in quantum-modified semiconductor media that incorporates microconcentration effects. The model extends classical photo-thermoelastic semiconductor theory by introducing a coupled dual-transport mechanism that accounts for quantum-modified carrier diffusion and thermodiffusion associated with microconcentration fields. Quantum transport is represented through a density-gradient formulation, enabling the capture of nonlocal carrier behavior at small length scales, while the microconcentration variable describes additional mass transport induced by temperature gradients. The governing equations for displacement, temperature, carrier density, and microconcentration are formulated within a unified continuum framework and reduced to dimensionless form in a one-dimensional configuration. The resulting system is solved analytically using the Laplace transform, and the physical fields are obtained in the time domain via numerical inversion. The analysis reveals that the interaction between quantum carrier transport and thermodiffusion significantly alters the propagation characteristics, leading to modified attenuation, phase behavior, and wave penetration depth. Furthermore, microconcentration introduces additional coupling that redistributes thermal and mechanical fields within the medium. The proposed formulation provides a comprehensive tool for understanding coupled transport phenomena in semiconductor structures and is relevant to applications in optoelectronic devices, nano-scale thermal management, and laser-driven material systems.